2015
DOI: 10.4049/jimmunol.1501927
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Amphioxus IFN Regulatory Factor Family Reveals an Archaic Signaling Framework for Innate Immune Response

Abstract: The IFN regulatory factor (IRF) family encodes transcription factors that play important roles in immune defense, stress response, reproduction, development, and carcinogenesis. Although the origin of the IRF family has been dated back to multicellular organisms, invertebrate IRFs differ from vertebrate IRFs in genomic structure and gene synteny, and little is known about their functions. Through comparison of multiple amphioxus genomes, in this study we suggested that amphioxus contains nine IRF members, whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, it has been shown that the IRF family members, along with the innate receptors such as TLRs, are found in animals other than vertebrates (Roach et al 2005;Nehyba et al 2009). It has been reported that the origin of the IRF family coincides with the appearance of multicellularity in animals (Nehyba et al 2009;Yuan et al 2015), and IRF genes are present in all principal metazoan groups. Interestingly, these genes are not found in the two groups that include most of metazoan species (i.e., roundworms and insects), suggesting that they disappeared during the evolution of these animals (Nehyba et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that the IRF family members, along with the innate receptors such as TLRs, are found in animals other than vertebrates (Roach et al 2005;Nehyba et al 2009). It has been reported that the origin of the IRF family coincides with the appearance of multicellularity in animals (Nehyba et al 2009;Yuan et al 2015), and IRF genes are present in all principal metazoan groups. Interestingly, these genes are not found in the two groups that include most of metazoan species (i.e., roundworms and insects), suggesting that they disappeared during the evolution of these animals (Nehyba et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To systematically identify previously unknown dsRNA sensors in amphioxus, we designed a proteomic screen using poly (I:C) agaroses and protein pull-down experiments. First, we cultured primary amphioxus intestine cells, as the digestive system is thought to comprise the major immune organs of amphioxus and contain many immune-related cells, including lymphocyte-like, monocyte-like, and macrophage-like cells (29, 30). Whole amphioxus intestine cell extracts were added to the poly(I:C) agaroses or control poly(C) agaroses followed by incubation at 4°C overnight.…”
Section: Resultsmentioning
confidence: 99%
“…The LGP2 (BjLGP2) gene of B. japonicum is predominantly expressed in the hepatic cecum, and up-regulated following challenge with poly I:C. In flounder gill cells, BjLGP2 has, upon poly I:C or viral challenge, the capacity to induce a RLRs signaling pathway via the interaction with MAVS which eventually leads to NF-κB-and IRF-3-dependent production of type I IFN and pro-inflammatory cytokines. In amphioxus, the key elements of the RLR signal transduction pathway, including MAVS, TBK1, IKK, STAT and IFN regulatory factors (IRFs), are present, but the canonical type I IFN is absent (Cao et al 2020;Liu et al 2015b;Yuan et al 2015b). Nevertheless, one of the vertebrate IFN-stimulated genes, viperin, has been identified in B. japonicum, and it been shown capable of attenuating viral infectivity and propagation (Lei et al 2015).…”
Section: Rig-i-like Receptorsmentioning
confidence: 99%